Bursera graveolens essential oil: Physicochemical characterization and antimicrobial activity in pathogenic microorganisms found in Kajikia audax (Scientia Agropecuaria, 2021)
Essential oils are products from aromatic plants, which, due to their biological, allelopathic, antioxidant and antimicrobial effects, are important for food preservation. Kajikia audax is a fish of great commercial importance, however, it is highly perishable, requiring strategies to extend its shelf life. In vitro antimicrobial activity of Bursera graveolens essential oil was determined against microorganisms isolated from K. audax. Essential oil was extracted by steam distillation, obtaining a yield of 1.25%, a density of 0.83 g/ml and a refractive index of 1.473°, in addition, it was determined by GC-MS that D-limonene (77.6%) is the majority compound. Antimicrobial tests showed that the minimum inhibitory concentration (MIC) for Aeromonas salmonicida and Pichia kudriavzevii was 1.62 mg/ml and 6.48 mg/ml respectively, and the minimum bactericidal concentration (MBC) was 25.92 mg/ml for both microorganisms. Pseudomonas aeruginosa showed total resistance against the concentrations used. B. graveolens essential oil turned out to be a potential product to control the growth of microorganisms isolated from K. audax, however, it should be tested against species of the genera Vibrio, Flavobacterium, Shewanella, Lactococcus and Streptococcus that cause spoiling of hydrobiological products.